THE DETERMINATION OF QUALITY AND BRAND IMAGES IN PURCHASING DECISION FOR SMEs CULINARY PRODUCTS - et al., Lucky Hikmat Maulana (International Journal of Advanced Science and Technology, 2020)
Specific culinary is one of the attractions offered and is the center of attention of tourists visiting a region. The majority of culinary producers are SMEs, which grow and have an impact on intense competition, especially in terms of quality and brand image. This study aims to determine the effect of product quality and brand image on purchasing decisions on UKM Culinary products. The population in this study was consumers, the dominant culinary being various foods such as cakes, brownies, bread, wet and dry cakes. Non-probability sampling method used in determining the sample. The method of data analysis uses multiple linear regression, correlation, determination, which then continued with the hypothesis test. The results showed that product quality and brand image had a positive and significant effect on purchasing decisions, both simultaneously and partially. It recommended that SMEs promote more actively through social media, exhibitions, and more stringent supervision of product safety, and further research carried out using different variables and methods